Perspective method for reconfigurable intelligent surface design for NOMA transmission: Theoretical study - Kontorovich, V. (Frontiers in Communications and Networks, 2023)
The method (paradigm) presented hereafter was inspired by two basic ideas: assumption of the MIMO-RIS-NOMA communication channel as a dispersive channel with fading and representation of the later by means of Generalized Kronecker Channel model (GKCM), applying the so-called “Orthogonalization Approach” based on the utilization of the “universal” eigen basis in the form of Prolate Spheroidal Wave Functions (PSWF). In other words, the essence of the approach is representing the MIMO-RIS-NOMA channel by means of a finite set of the artificially created orthogonal trajectories for wave propagation, being connected between themselves by the so-called Coupling Matrix (CM) of the RIS. The goal for RIS (by certain choice of the CM elements) is to provide a decoding system for the NOMA users with the required SNR values for each user to guarantee its successful decoding processing. The theoretical analysis of this paradigm is presented in the ongoing material.